Urban green space for health and well-being: developing an 'affordances' framework for planning and design - Lennon, Mick; Douglas, Owen; Scott, Mark (Journal of urban design, 2017)
A vast literature exploring environmental influences on human health and well-being has provided renewed interest in connecting planning for the built environment with health initiatives. In response, planners and urban designers have been tasked with translating this knowledge into spatial planning and design schemes. This paper responds to an identified need for a conceptually-informed framework for green space planning and design for health and well-being that moves beyond attribute-descriptive studies. The notion of an 'affordances star' is proposed as a means to maximize the functionality and inclusivity of green space for health and well-being.